ASSESSMENT MODEL MUKA AIR TANAH PADA PERTANAMAN KELAPA SAWIT DI LAHAN BERBUKIT - Iman Yani Harahap; M. Edwin Syahputra Lubis (Pusat Penelitian Kelapa Sawit, 2017)
The aim of this research is to assess performance of developed water table model on oil palm area in a hilly land. The model requires some data of initiatial condition, input model, and physical parameters of the soils and crops. Initial data includes leaf area index, latitude geography position, initial water table, and the deep of impermeable soil layer. Input model includes daily weather data (rainfall, temperature, solar radiation, and wind speed). Soil physic parameters includes bulk volum density at each soil layers, and run-off of the soil surface. The crop parameters includes rainfall interception of crown and stem plants. Daily water table measurement was carried out at 3 points of wells located in one line hilly catena (30 – 70 m above sea level) with slope about of 15% (top, middle, and foot). The area was the 20 years old oil palm planting area, soil type was Typic Hapludult with coarse to fine soil texture, hydraulic conductivity was classified as fast. The water table in this area was located in unconfined aquifer zone. The results showed that outputs of the model were 3 - 4% higher than the actual values observed on the top hill, 7 – 8% lower than the actual values on the middle sloping of the hill, and 7 – 7.5% lower than the actual values on the foot hill. The high rate of run-off at the top might have reduced the water inflow (through infiltration process) to the system, causing output values of the model were higher than the actual values. On the other hand, the water inflow from the top to the lower area might have increased the water inflow to the system, so that the actual values were higher than the output values of the water table model. Adjustments of parameters mainly run-off rate and hydraulic potential gradient on sloping and hilly physiography might increase the accuracy of the model.